Method for manufacturing single-oriented ceramic fiber prepreg and single-oriented ceramic fiber prepreg

The method addresses the challenge of achieving a dense matrix structure in ceramic-based composite materials by orienting ceramic fibers and immersing them in a ceramic particle-containing composition, resulting in improved mechanical properties and suitability for diverse applications.

JP2025059485APending Publication Date: 2025-04-10FUJIMI INCORPORATED
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023169589
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing methods for manufacturing ceramic-based composite materials face challenges in achieving a dense matrix structure due to poor impregnation of the matrix between nonwoven fabric fibers, leading to internal air bubbles and reduced mechanical properties.

Method used

A method involving the orientation of ceramic fibers and a ceramic particle-containing composition in one direction, followed by coating the composition onto a support, immersing the fibers into the coating film, and drying to produce a one-way ceramic fiber prepreg with improved impregnation and dispersibility.

Benefits of technology

The method achieves a prepreg with a dense matrix structure, enhancing the mechanical properties of ceramic matrix composites, which are suitable for various applications such as electronic components and high-temperature structural members.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059485000001_ABST
    Figure 2025059485000001_ABST
Patent Text Reader

Abstract

To provide means for obtaining a prepreg which has improved impregnability into a nonwoven fiber of a matrix and has a dense matrix structure.SOLUTION: The present invention provides a method for manufacturing a single-oriented ceramic fiber prepreg, comprising the steps of: preparing a plurality of ceramic fibers oriented in a single direction and a ceramic particle-containing composition; coating the ceramic particle-containing composition on a support to obtain a coated film; immersing the plurality of ceramic fibers oriented in the single direction into the coated film to obtain a ceramic particle-containing composition-impregnated body; and drying the ceramic particle-containing composition-impregnated body, and then peeling off the support, thereby obtaining the single-oriented ceramic fiber prepreg.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a unidirectional ceramic fiber prepreg and a unidirectional ceramic fiber prepreg. [Background technology]

[0002] Depending on the type, ceramic materials have advantages such as excellent hardness, mechanical strength, heat resistance, impact resistance, wear resistance, oxidation resistance, or corrosion resistance, or a small thermal expansion coefficient, etc. For these reasons, ceramic materials are expected to be used in a variety of applications such as electronic components and high-temperature structural members.

[0003] Ceramic materials are sometimes used as composite materials of a plurality of ceramic materials or composite materials of ceramic and other materials for the purpose of further improving functionality, production efficiency, etc. Examples of such composite materials include those formed using prepregs containing ceramic fibers and ceramic particles.

[0004] For example, Patent Document 1 discloses a method for producing a ceramic-based composite material member, which includes a slurry preparation step of preparing a slurry in which an oxide-based ceramic powder is dispersed in a dispersion medium, and an impregnation step of impregnating a sheet made of inorganic fibers with the slurry to form a slurry-impregnated sheet. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6978896 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the method described in Patent Document 1 has a problem in that the matrix does not penetrate between the fibers of the nonwoven fabric well, and internal air bubbles are formed, making it impossible to obtain a prepreg having a dense matrix structure.

[0007] Therefore, an object of the present invention is to provide a means for improving the impregnation of the matrix into the spaces between the fibers of the nonwoven fabric and obtaining a prepreg having a dense matrix structure. [Means for solving the problem]

[0008] In order to solve the above problems, the present invention provides a method for producing a unidirectional ceramic fiber prepreg, comprising the steps of: preparing a plurality of unidirectionally oriented ceramic fibers and a ceramic particle-containing composition; applying the ceramic particle-containing composition onto a support to obtain a coating film; immersing the plurality of unidirectionally oriented ceramic fibers into the coating film to obtain a ceramic particle-containing composition-impregnated body; and drying the ceramic particle-containing composition-impregnated body and then peeling off the support to obtain a unidirectional ceramic fiber prepreg.

[0009] The present invention also provides a unidirectional ceramic fiber prepreg comprising a plurality of ceramic fibers oriented in one direction and a ceramic particle-containing composition impregnated into the plurality of ceramic fibers, wherein a coefficient of variation in the number of the ceramic fibers per unit section in a cut section along a thickness direction of the unidirectional ceramic fiber prepreg is 2.0 or less. Effect of the Invention

[0010] According to the present invention, there is provided a means for improving the impregnation of the matrix into spaces between the fibers of the nonwoven fabric, thereby enabling a prepreg having a dense matrix structure to be obtained. [Brief description of the drawings]

[0011] [Figure 1]FIG. 2 is a SEM photograph of a cross section cut in the thickness direction of the unidirectional ceramic fiber prepreg obtained in the example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] According to one embodiment of the present invention, there is provided a method for producing a unidirectional ceramic fiber prepreg, the method including the steps of preparing a plurality of ceramic fibers oriented in one direction and a ceramic particle-containing composition, applying the ceramic particle-containing composition onto a support to obtain a coating film, immersing the plurality of ceramic fibers oriented in one direction into the coating film to obtain a ceramic particle-containing composition-impregnated body, and drying the ceramic particle-containing composition-impregnated body and peeling off the support to obtain a unidirectional ceramic fiber prepreg. According to another embodiment of the present invention, there is provided a unidirectional ceramic fiber prepreg including a plurality of ceramic fibers oriented in one direction and a ceramic particle-containing composition impregnated into the plurality of ceramic fibers, the coefficient of variation of the number of the ceramic fibers per unit section in a cut surface along the thickness direction of the unidirectional ceramic fiber prepreg is 2.0 or less.

[0013] In this specification, the term "prepreg" refers to a composite material in a semi-cured state produced by impregnating a plurality of unidirectionally oriented ceramic fibers with a ceramic particle-containing composition.

[0014] The manufacturing method described in the above Patent Document 1 includes a step of preparing an immersion bath containing a slurry in which an oxide-based ceramic powder is dispersed in a dispersion medium, and then immersing a sheet made of inorganic fibers in the immersion bath to impregnate the spaces between the fibers of the sheet with the slurry. However, this method has a problem in that the inorganic fibers contained in the sheet have a high degree of adhesion and restraint between each other, making it difficult for the slurry to penetrate into the inside of the sheet.

[0015] To solve this problem, a method of inserting a plurality of ceramic fibers oriented in one direction (hereinafter, simply referred to as "unidirectional ceramic fibers") into an immersion bath of a slurry and impregnating the inside of the unidirectional ceramic fibers with the slurry can be considered. However, the present inventors have found that when this method is performed, problems can arise such as the formation of fiber bundles and gaps when the fibers are pulled out of the immersion bath, and internal bubbles are formed, making it impossible to obtain a prepreg having a dense matrix structure.

[0016] In view of the above problems, the present inventors have conducted extensive research. As a result, the present inventors have found that a prepreg having excellent dispersibility of unidirectional ceramic fibers can be obtained by a manufacturing method including forming a coating film made of a composition (slurry) containing ceramic particles in advance and immersing unidirectional ceramic fibers in the coating film. According to this method, a prepreg having improved dispersibility of unidirectional ceramic fibers, in which the coefficient of variation of the number of ceramic fibers per unit section is 2.0 or less, can be obtained in a very simple manner. The obtained prepreg has a dense matrix structure. As a result, it is expected that a ceramic matrix composite material (CMC) obtained by sintering the prepreg or the like will have excellent mechanical properties. Therefore, such a CMC is suitable for a wide range of applications, such as electronic components and high-temperature structural members.

[0017] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to the following embodiments and can be modified in various ways within the scope of the claims. The embodiments described in this specification can be arbitrarily combined to form other embodiments.

[0018] In this specification, unless otherwise specified, operations and measurements of physical properties are performed under conditions of room temperature (20° C. or higher and 25° C. or lower) and relative humidity of 40% RH or higher and 50% RH or lower.

[0019] [Coefficient of variation] In the unidirectional ceramic fiber prepreg according to one embodiment of the present invention, the coefficient of variation of the number of unidirectional ceramic fibers per unit section in the cut surface along the thickness direction is 2.0 or less. If the coefficient of variation is 2.0 or less, a prepreg having a dense matrix structure can be obtained. The smaller the coefficient of variation, the more evenly the unidirectional ceramic fibers are dispersed in the prepreg, suggesting that a prepreg having a denser matrix structure can be obtained, and thus a ceramic-based composite material having excellent mechanical properties can be obtained. On the other hand, if the coefficient of variation exceeds 2.0, the fibers are bundled or gaps are formed, and internal bubbles are formed, so that a prepreg having a dense matrix structure cannot be obtained. The coefficient of variation is preferably 1.7 or less, more preferably 1.5 or less.

[0020] In this specification, the coefficient of variation is calculated by the following method. That is, the unidirectional ceramic fiber prepreg is cut along the thickness direction, and an image of the cut surface is taken using a low vacuum scanning electron microscope. As an example, the area to be photographed is 192 μm long x 256 μm wide. The obtained image is divided vertically into four parts relative to the entire thickness of the prepreg, and divided horizontally into four parts with a width of 256 μm. This results in a total of 16 sections, and the number of ceramic fibers per section is measured for each of the sections obtained (a total of 16 sections are measured). The standard deviation and average value of the number of ceramic fibers at 16 points are calculated, and the value obtained by dividing the standard deviation by the average value is taken as the coefficient of variation. More specifically, the coefficient of variation can be measured by the method described in the Examples.

[0021] The coefficient of variation can be controlled by adjusting the viscosity of the ceramic particle-containing composition with which the unidirectional ceramic fibers are impregnated, the immersion time, the fiber extension tension, and the like.

[0022] [Ceramic fiber] The ceramic fibers according to one embodiment of the present invention are oriented in one direction, improving the mechanical properties of the prepreg. The orientation direction of the ceramic fibers may be the same as the longitudinal direction of the prepreg according to the present invention. The ceramic fibers are not particularly limited as long as they are fibers that are substantially made of ceramic. Here, the content of ceramic in the unidirectional ceramic fibers is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 100 mass% (upper limit 100 mass%), based on the total mass of the unidirectional ceramic fibers. The content of ceramic in the unidirectional ceramic fibers can be evaluated by weight change by thermogravimetric analysis, etc.

[0023] The ceramic constituting the unidirectional ceramic fiber is not particularly limited, and may be any material used in known ceramic fibers. Examples include glass, silicon carbide, alumina, silica, mullite, carbon, etc. Examples include oxides or composite oxides of Si, Ti, Zr, Mg, Hf, Al, and rare earth elements described in International Publication No. 2012 / 077787. The ceramic constituting the unidirectional ceramic fiber may be used alone or in combination of two or more. The ceramic fiber is more preferably silicon carbide (SiC) fiber, alumina fiber, mullite fiber, or carbon fiber.

[0024] The unidirectional ceramic fibers may be commercially available or manufactured. The method for obtaining the manufactured products is not particularly limited, and for example, the products may be obtained by opening a ceramic fiber bundle. The opening method may be a known method alone or a combination of multiple methods.

[0025] The ceramic fibers may be used alone or in combination of two or more kinds. The average fiber length, average fineness, etc. of the ceramic fibers may be appropriately changed depending on the application.

[0026] The fiber content (Vf) of the unidirectional ceramic fibers in the prepreg according to the present invention is preferably 20% by volume or more, more preferably 25% by volume or more, and even more preferably 30% by volume or more. The fiber content (Vf) of the unidirectional ceramic fibers in the prepreg according to the present invention is preferably 85% by volume or less, more preferably 80% by volume or less, and even more preferably 75% by volume or less. That is, the fiber content (Vf) of the unidirectional ceramic fibers in the prepreg according to the present invention is preferably 20% by volume or more and 85% by volume or less, more preferably 25% by volume or more and 80% by volume or less, and even more preferably 30% by volume or more and 75% by volume or less. If the fiber content (Vf) is within such a range, the number of fibers in the prepreg becomes appropriate, and there is no adhesion between the fibers or no fiber-deficient areas, so that there is an advantage in that local destruction after the final formation of the sintered body can be prevented. The fiber content (Vf) can be obtained by a calculation method according to ASTM D3171 or JIS K7075:1991. The fiber content (Vf) can be controlled by adjusting the thickness of the coating film produced from the ceramic particle-containing composition in the production method described below, the basis weight of the fibers used, the solids concentration of the slurry, etc.

[0027] [Ceramic particle-containing composition] The unidirectional ceramic fiber prepreg according to the present invention includes a ceramic particle-containing composition (hereinafter, also simply referred to as "composition") impregnated into a plurality of unidirectional ceramic fibers. The ceramic particle-containing composition generally includes (A) ceramic particles, (B) binder, (C) plasticizer, (D) water, and, if necessary, further includes (E) acid, (F) thickener, (G) other components, etc. These components will be described below.

[0028] <(A) Ceramic particles> A ceramic particle-containing composition according to one embodiment of the present invention contains ceramic particles as component (A). In this specification, the term "ceramic particles" refers to particles containing ceramic.

[0029] The ceramic content relative to the total mass of the ceramic particles that can be used as component (A) is not particularly limited, but is preferably 50 mass% or more, more preferably 70 mass% or more, and even more preferably 90 mass% or more (upper limit 100 mass%). The ceramic content can be evaluated from the weight change by thermogravimetric analysis.

[0030] The type of ceramic contained in the ceramic particles used as component (A) is not particularly limited. Examples of the ceramic contained in the ceramic particles include compounds composed only of carbon, oxides, hydroxides, carbides, carbonates, nitrides, halides, phosphates, borides, etc. Examples of oxides include, but are not particularly limited to, silicon oxide, aluminum oxide (alumina, Al2O3), mullite, copper oxide, iron oxide, nickel oxide, tin oxide, cadmium oxide, zinc oxide, zirconium oxide, etc. Examples of hydroxides include, but are not particularly limited to, aluminum hydroxide (Al(OH)3), etc. Examples of carbides include, but are not particularly limited to, silicon carbide (SiC), boron carbide, etc. Examples of nitrides include, but are not particularly limited to, silicon nitride, gallium nitride, titanium nitride, lithium nitride, etc. Examples of the ceramic contained in the ceramic particles include oxides or composite oxides of Si, Ti, Zr, Mg, Hf, Al, and rare earth elements, as described in International Publication No. 2012 / 077787. The ceramic particles may contain these ceramics alone or in combination of two or more kinds.

[0031] In a preferred embodiment of the present invention, component (A) includes ceramic particles containing at least one selected from the group consisting of oxides, carbides, nitrides, and borides. The content ratio of the ceramic particles containing at least one selected from the group consisting of oxides, carbides, nitrides, and borides to the total mass of component (A) is preferably 50 mass% or more, more preferably 90 mass% or more (upper limit 100 mass%). It is further preferable that the ceramic particles of component (A) are ceramic particles containing at least one selected from the group consisting of oxides, carbides, nitrides, and borides.

[0032] In a more preferred embodiment of the present invention, component (A) includes ceramic particles containing at least one selected from the group consisting of oxides and carbides. The content ratio of the ceramic particles containing at least one selected from the group consisting of oxides and carbides to the total mass of component (A) is preferably 50 mass% or more, more preferably 90 mass% or more (upper limit 100 mass%), relative to the total mass of component (A). It is further preferred that the ceramic particles of component (A) are ceramic particles containing at least one selected from the group consisting of oxides and carbides.

[0033] In a further preferred embodiment of the present invention, the carbide-containing ceramic particles include silicon carbide-containing ceramic particles. The content ratio of the silicon carbide-containing ceramic particles to the total mass of the carbide-containing ceramic particles is preferably 50 mass% or more, more preferably 90 mass% or more (upper limit 100 mass%). It is further preferred that the carbide-containing ceramic particles in component (A) are silicon carbide-containing ceramic particles.

[0034] In a further preferred embodiment of the present invention, the oxide-containing ceramic particles include ceramic particles containing at least one selected from the group consisting of alumina and mullite. The content ratio of the ceramic particles containing at least one selected from the group consisting of alumina and mullite to the total mass of the oxide-containing ceramic particles is preferably 50 mass% or more, more preferably 90 mass% or more (upper limit 100 mass%). It is further preferred that the oxide-containing ceramic particles in component (A) are ceramic particles containing at least one selected from the group consisting of alumina and mullite.

[0035] The ceramic particles that can be used as the component (A) may be uncoated particles, particles coated with a coating layer (coated particles), or a combination thereof. Here, "coated" means that at least a part of the particles is coated with a coating layer. The coating layer is not particularly limited, but a coating layer containing aluminum hydroxide is preferable. The coating method is not particularly limited, and a known method can be used. The silicon carbide particles coated with a coating layer containing aluminum hydroxide are not particularly limited, but can be produced by appropriately adopting the methods and conditions described in, for example, International Publication No. 2019 / 065956. In addition, the composition and structure of the coated particles can be analyzed, for example, by SEM (Scanning Electron Microscope)-EDX (Energy Dispersive X-ray Spectroscopy) observation, TEM (Transmission Electron Microscope)-EDX (Energy Dispersive X-ray Spectroscopy) observation, EELS (Electron Energy Loss Spectroscopy) analysis, or by combining multiple measurements as necessary.

[0036] The ceramic particles that can be used as component (A) may be surface-treated. The type and method of the surface treatment are not particularly limited, and any known type and method of surface treatment can be appropriately adopted.

[0037] Preferred examples of the (A) component include oxide particles, carbide particles, oxide particles coated with a coating layer, and carbide particles coated with a coating layer. Specific examples are not particularly limited, but include silicon oxide particles, mullite particles, alumina particles, copper oxide particles, iron oxide particles, nickel oxide particles, tin oxide particles, cadmium oxide particles, zinc oxide particles, zirconium oxide particles, silicon carbide particles, boron carbide particles, and particles coated with a coating layer. Among these, mullite particles, alumina particles, silicon carbide particles, and silicon carbide particles coated with a coating layer containing aluminum hydroxide (aluminum hydroxide-coated SiC particles) are more preferred. In addition, at least one selected from the group consisting of alumina particles, silicon carbide particles, and silicon carbide particles coated with a coating layer containing aluminum hydroxide (aluminum hydroxide-coated SiC particles) is more preferred, and aluminum hydroxide-coated SiC particles are particularly preferred.

[0038] The shape of the ceramic particles that can be used as component (A) is not particularly limited, and may be spherical or non-spherical. Specific examples of non-spherical shapes include polygonal prisms such as triangular prisms and square prisms, cylinders, bales in which the center of a cylinder is bulging out more than the ends, donuts in which the center of a disk is penetrated, plates, so-called cocoon shapes with a constriction in the center, so-called association-type spheres in which multiple particles are integrated, beads-shaped shapes in which multiple particles are connected in a line, so-called confetti-shaped shapes with multiple protrusions on the surface, rugby ball shapes, and needle-shaped shapes that are even thinner than the rugby ball shapes, and are not particularly limited.

[0039] The average primary particle size of the ceramic particles that can be used as component (A) is not particularly limited, but is preferably 0.001 μm or more, more preferably 0.005 μm or more, and even more preferably 0.01 μm or more. Within these ranges, the aggregation of the ceramic particles is more suppressed, and a composition with higher dispersibility is obtained. The average primary particle size of the ceramic particles that can be used as component (A) is not particularly limited, but is preferably 2.0 μm or less, more preferably 1.5 μm or less, even more preferably 1.0 μm or less, and especially preferably 0.5 μm or less. Within such ranges, the settling of the ceramic particles is more suppressed, and a composition with higher dispersibility is obtained. The average primary particle size of the ceramic particles can be calculated based on the average value of the specific surface area (SA) of the ceramic particles calculated from the values ​​measured three times consecutively by the BET method, using the value of the true density of the ceramic particles, and assuming that the shape of the ceramic particles is a true sphere. The measurement of the specific surface area of ​​the ceramic particles can be performed, for example, using Flow SorbII 2300 manufactured by Micromeritics. In view of the above, examples of the range of the average primary particle size of the ceramic particles that can be used as component (A) include, but are not limited to, 0.001 μm or more and 2.0 μm or less, 0.005 μm or more and 1.5 μm or less, 0.01 μm or more and 1.0 μm or less, and 0.01 μm or more and 0.5 μm or less.

[0040] The average secondary particle diameter of the ceramic particles used as component (A) is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.03 μm or more, even more preferably 0.05 μm or more, and particularly preferably 0.1 μm or more. Within these ranges, the possibility of excessive thickening of the composition is further reduced, and a composition more suitable for coating is obtained. The average secondary particle diameter of the ceramic particles that can be used as component (A) is not particularly limited, but is preferably 3 μm or less, more preferably 2 μm or less, even more preferably 1.5 μm or less, and particularly preferably 1 μm or less. Within these ranges, the settling of the ceramic particles is further suppressed, and a composition with higher dispersibility is obtained. The value of the average secondary particle diameter of the ceramic particles can be measured using a scattering type particle size distribution measuring device LA-950 manufactured by Horiba, Ltd. In view of the above, examples of the range of the average secondary particle size of the ceramic particles that can be used as component (A) include, but are not limited to, 0.01 μm or more and 3 μm or less, 0.03 μm or more and 2 μm or less, 0.05 μm or more and 1.5 μm or less, and 0.1 μm or more and 1 μm or less.

[0041] The component (A) may be a commercially available product or a synthetic product. When the ceramic particles are coated particles, the pre-coated particles that are the raw material for the coated particles may also be commercially available products or synthetic products. The commercially available pre-coated particles are not particularly limited, but examples thereof include products manufactured by Fujimi Incorporated under the product name WA#30000 and the product name GC#40000.

[0042] As the component (A), one type of ceramic particles may be used alone, or two or more types of ceramic particles may be used in combination.

[0043] The content of the (A) component in the ceramic particle-containing composition is not particularly limited, but is preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 10% by mass or more, based on the total mass of the solid content in the composition. In this range, the amount of other components removed during drying, degreasing, etc. is reduced, resulting in a composition that is superior in terms of production costs. In addition, the content of the (A) component in the composition is not particularly limited, but is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less, based on the total mass of the solid content in the composition. In this range, the possibility of excessive thickening of the composition is further reduced, and a composition that is more suitable for coating is obtained. From these points of view, examples of the range of the content of the (A) component in the ceramic particle-containing composition include, but are not limited to, 0.1% by mass or more and 90% by mass or less, 1% by mass or more and 80% by mass or less, and 10% by mass or more and 75% by mass or less, based on the total mass of the solid content in the composition. When the composition contains two or more types of component (A), the content of component (A) refers to the total amount of these.

[0044] The ceramic particle-containing composition may contain particles containing boron nitride (BN), but may not substantially contain particles containing BN, or may not contain any particles containing BN at all. In this specification, "substantially free of particles containing BN" means that the content of particles containing BN in the ceramic particle-containing composition is less than 0.1 mass% with respect to the total mass of the composition. The ceramic particle-containing composition may contain particles containing silicon carbide (SiC), but may not substantially contain particles containing SiC, or may not contain any particles containing SiC at all. In this specification, "substantially free of particles containing SiC" means that the content of particles containing SiC in the ceramic particle-containing composition is less than 0.1 mass% with respect to the total mass of the composition.

[0045] <Component (B): Binder> The ceramic particle-containing composition according to one embodiment of the present invention contains a binder (binder resin) as component (B), which can improve the moldability and handling properties of the prepreg.

[0046] The (B) component is not particularly limited, and known resins can be used. Among these, from the viewpoint of obtaining excellent dispersibility and high stability over time, a resin having a hydroxyl group (hereinafter also referred to as (B1) component) is preferred. As the (B1) component, preferred examples include polyvinyl alcohol (PVA); modified polyvinyl alcohol (modified PVA) such as polyvinyl butyral (PVB), polyvinyl propylal, polyvinyl acetal, and polyvinyl formal, hydroxyl group-containing glyoxal resin, hydroxyl group-containing acrylic resin, phenol resin, hydroxyl group-containing polyvinyl pyrrolidone (PVP), hydroxyl group-containing polyester, hydroxyl group-containing silicone, and hydroxyl group-containing polycarboxylic acid, but are not limited thereto. Among these, from the viewpoint of ease of handling and ease of viscosity adjustment, polyvinyl alcohol and modified polyvinyl alcohol are more preferred, polyvinyl alcohol, polyvinyl butyral, and polyvinyl acetal are even more preferred, and polyvinyl acetal is particularly preferred.

[0047] In a preferred embodiment of the present invention, the (B) component contains a (B1) component: a resin having a hydroxyl group. The content of the (B1) component relative to the total mass of the (B) component is preferably 50% by mass or more, and more preferably 90% by mass or more (upper limit 100% by mass). The binder of the (B) component is more preferably the (B1) component.

[0048] In a further preferred embodiment of the present invention, the (B1) component: a resin having a hydroxyl group includes at least one resin (hereinafter also referred to as (B2) component) selected from the group consisting of polyvinyl alcohol (PVA), polyvinyl butyral (PVB), polyvinyl propylar, polyvinyl acetal, polyvinyl formal, hydroxyl group-containing glyoxal resin, hydroxyl group-containing acrylic resin, phenol resin, hydroxyl group-containing polyvinylpyrrolidone (PVP), hydroxyl group-containing polyester, hydroxyl group-containing silicone, and hydroxyl group-containing polycarboxylic acid. The content ratio of the (B2) component to the total mass of the (B1) component is preferably 50 mass% or more, more preferably 90 mass% or more (upper limit 100 mass%). The (B1) component: a resin having a hydroxyl group in the (B) component is more preferably the (B2) component. It is particularly preferable that the resin that is the (B) component is the (B2) component.

[0049] The weight average molecular weight of the binder that can be used as the (B) component is not particularly limited, but is preferably 1,000 or more, more preferably 2,000 or more, and even more preferably 5,000 or more. Within these ranges, a composition that can further improve the moldability of the prepreg can be obtained. The weight average molecular weight of the binder that can be used as the (B) component is not particularly limited, but is preferably 500,000 or less, more preferably 100,000 or less, and even more preferably 50,000 or less. Within such a range, the possibility of excessive thickening of the composition is further reduced, and a composition that is more suitable for coating can be obtained. The value of the weight average molecular weight of the binder can be measured by gel permeation chromatography (GPC), specifically, it can be measured by the method described in the examples. For these reasons, examples of the range of the weight average molecular weight of the resin that can be used as component (B) include, but are not limited to, 1,000 or more and 500,000 or less, 2,000 or more and 100,000 or less, and 5,000 or more and 50,000 or less.

[0050] The component (B) may be a commercially available product or a synthetic product. The commercially available product is not particularly limited, but an example thereof is S-LEC (registered trademark) KW-3 manufactured by Sekisui Chemical Co., Ltd.

[0051] As the component (B), one type of resin may be used alone, or two or more types of resins may be used in combination.

[0052] The content of the (B) component in the ceramic particle-containing composition is not particularly limited, but is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 1% by mass or more, based on the total mass of the composition. Within this range, a composition that can improve the moldability of the prepreg can be obtained. The content of the (B) component in the ceramic particle-containing composition is not particularly limited, but is preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 25% by mass or less, based on the total mass of the composition. Within this range, the amount of other components removed during drying, degreasing, etc. is reduced, and a composition that is superior in terms of production costs can be obtained. From these points of view, examples of the range of the content of the (B) component in the ceramic particle-containing composition include, but are not limited to, 0.01% by mass or more and 50% by mass or less, 0.1% by mass or more and 30% by mass or less, and 1% by mass or more and 25% by mass or less, based on the total mass of the composition. In addition, when the composition contains two or more types of (B) components, the content of the (B) component refers to the total amount of these.

[0053] The content ratio of the (A) component and the (B) component is not particularly limited. The content of the (B) component is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, even more preferably 2.5 parts by mass or more, and particularly preferably 5 parts by mass or more, relative to 100 parts by mass of the (A) component. Within this range, a composition with better moldability of the prepreg can be obtained. The content of the (B) component is preferably 1,000 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 50 parts by mass or less, relative to 100 parts by mass of the (A) component. Within this range, the amount of resin component removed during degreasing is reduced, and a composition with better manufacturing cost can be obtained. For these reasons, the content of the (B) component can be, relative to 100 parts by mass, 0.1 parts by mass or more to 1,000 parts by mass or less, 1 part by mass or more to 100 parts by mass or less, 2.5 parts by mass or more to 50 parts by mass or less, 5 parts by mass or more to 50 parts by mass or less, etc., but is not limited thereto.

[0054] <Component (C): Plasticizer> The ceramic particle-containing composition according to one embodiment of the present invention preferably contains a plasticizer as component (C). Component (C) can increase the flexibility of the prepreg. In this specification, the plasticizer refers to a compound having a function of increasing the flexibility of the prepreg according to the present invention.

[0055] The (C) component is not particularly limited, and known plasticizers can be used. Among such plasticizers, from the viewpoint of dispersibility in the composition, preferred examples include water-soluble plasticizers such as ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, glycerin, and triethanolamine, and phthalate ester plasticizers such as dibutyl phthalate, which are insoluble in water and move into an emulsion, but are not limited thereto. From the same viewpoint, the (C) component is more preferably a water-soluble plasticizer, more preferably a water-soluble plasticizer that is a polymer, and even more preferably diethylene glycol, triethylene glycol, and polyethylene glycol, and particularly preferably polyethylene glycol. Diethylene glycol, triethylene glycol, and polyethylene glycol are polymers of two, three, and four or more ethylene glycols, respectively.

[0056] In a preferred embodiment of the present invention, the (C) component contains at least one compound selected from the group consisting of ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, glycerin, triethanolamine, and dibutyl phthalate (hereinafter also referred to as (C1) component). The content of the (C1) component relative to the total mass of the (C) component is preferably 50 mass% or more, and more preferably 90 mass% or more (upper limit 100 mass%). It is further preferable that the plasticizer of the (C) component is the (C1) component.

[0057] In a more preferred embodiment of the present invention, the (C) component contains at least one compound selected from the group consisting of diethylene glycol, triethylene glycol, and polyethylene glycol. The content of the at least one compound selected from the group consisting of diethylene glycol, triethylene glycol, and polyethylene glycol relative to the total mass of the (C) component is preferably 50% by mass or more, and more preferably 90% by mass or more (upper limit 100% by mass). The (C) component plasticizer is further preferably at least one compound selected from the group consisting of diethylene glycol, triethylene glycol, and polyethylene glycol.

[0058] The molecular weight of the plasticizer that can be used as the (C) component is not particularly limited, but is preferably smaller than the molecular weight of the binder, which is the (B) component. The molecular weight of the plasticizer calculated from the sum of atomic weights is preferably less than 1,000. In addition, for example, when the hydroxyl value of the plasticizer can be measured by neutralization titration method, the average molecular weight calculated from the hydroxyl value measurement result of the plasticizer by neutralization titration method is preferably less than 1,000. The average molecular weight calculated from the hydroxyl value measurement result of the plasticizer by neutralization titration method can be calculated based on JIS K 0070:1992. Within these ranges, the effect of the plasticizer is further improved.

[0059] In a preferred embodiment of the present invention, it is preferred that the binder, component (B), is a resin having a weight average molecular weight of 1,000 or more, and the plasticizer, component (C), is a plasticizer having an average molecular weight of less than 1,000 calculated from the results of hydroxyl value measurement by neutralization titration method.

[0060] The plasticizer that can be used as the component (C) may be a commercially available product or a synthetic product. The commercially available product is not particularly limited, but an example thereof is polyethylene glycol 200 manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.

[0061] As the component (C), one type of plasticizer may be used alone, or two or more types of plasticizers may be used in combination.

[0062] The content of the (C) component in the ceramic particle-containing composition is not particularly limited, but is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 1% by mass or more, based on the total mass of the composition. In such a range, a composition that can give excellent flexibility to the prepreg is obtained. The content of the (C) component in the ceramic particle-containing composition is not particularly limited, but is preferably 50% by mass or less, more preferably 25% by mass or less, and even more preferably 10% by mass or less, based on the total mass of the composition. In this range, the amount of plasticizer component removed in degreasing is reduced, and a composition that is superior in terms of production costs is obtained. For these reasons, the content of the (C) component in the ceramic particle-containing composition may be 0.01% by mass or more and 50% by mass or less, 0.1% by mass or more and 25% by mass or less, 1% by mass or more and 10% by mass or less, based on the total mass of the composition, but is not limited thereto. In addition, when the composition contains two or more kinds of (C) components, the content of the (C) component refers to the total amount of these.

[0063] The content ratio of the (C) component to the (A) component is not particularly limited. The content of the (C) component is preferably 0.1 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 2.5 parts by mass or more, relative to 100 parts by mass of the (A) component. Within this range, a composition that can impart excellent flexibility to the prepreg is obtained. Furthermore, the content of the (C) component is preferably 1,000 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 50 parts by mass or less, relative to 100 parts by mass of the (A) component. Within this range, the amount of plasticizer component removed during degreasing is reduced, and a composition that is superior in terms of production costs is obtained. For these reasons, the content of the (C) component may be, relative to 100 parts by mass, 0.1 parts by mass or more to 1,000 parts by mass or less, 1 part by mass or more to 100 parts by mass or less, 2.5 parts by mass or more to 50 parts by mass or less, etc., but is not limited thereto.

[0064] The content ratio of the (B) component to the (C) component is not particularly limited, but the content of the (B) component is preferably 50 parts by mass or more, more preferably 100 parts by mass or more, and even more preferably 150 parts by mass or more, relative to 100 parts by mass of the (C) component. The content of the (B) component is preferably 600 parts by mass or less, more preferably 500 parts by mass or less, and even more preferably 400 parts by mass or less, relative to 100 parts by mass of the (C) component. If it is within such a range, the state of hardening of the green sheet by the binder and the state of imparting flexibility to the green sheet by the plasticizer are properly maintained, and the advantages of preventing cracks and breaks at the time of finishing and facilitating handling are obtained. For these reasons, the content of the (B) component may be, relative to 100 parts by mass, 50 parts by mass or more and 600 parts by mass or less, 100 parts by mass or more and 500 parts by mass or less, 150 parts by mass or more and 400 parts by mass or less, etc., but is not limited thereto.

[0065] <(D) Ingredient: Water> The ceramic particle-containing composition according to one embodiment of the present invention preferably contains water as component (D). Component (D) is preferably water that contains as few impurities as possible, and more preferably water with a total transition metal ion content of 100 ppb or less. The purity of the water that can be used as component (D) can be increased by, for example, removing impurity ions using ion exchange resins, removing foreign matter using a filter, distillation, or other operations. Specifically, it is preferable to use, for example, deionized water (ion-exchanged water), pure water, ultrapure water, distilled water, or the like as component (D).

[0066] <(E) component: acid> The ceramic particle-containing composition according to one embodiment of the present invention may further contain an acid as component (E). Component (E) is used as a pH adjuster and can further lower the pH of the composition.

[0067] The component (E) is not particularly limited, and a known acid can be used. The component (E) may be either an organic acid or an inorganic acid. The acid is preferably a non-polymeric acid. The non-polymeric acid is preferably a compound having a total atomic weight of less than 1,000.

[0068] The organic acid is not particularly limited, but examples thereof include carboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, n-hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylpentanoic acid, n-heptanoic acid, 2-methylhexanoic acid, n-octanoic acid, 2-ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, citric acid, lactic acid, diglycolic acid, 2-furancarboxylic acid, 2,5-furandicarboxylic acid, 3-furancarboxylic acid, 2-tetrahydrofurancarboxylic acid, methoxyacetic acid, methoxyphenylacetic acid, and phenoxyacetic acid; and sulfur-containing organic acids such as methanesulfonic acid, ethanesulfonic acid, and isethionic acid. The inorganic acid is not particularly limited, but examples thereof include carbonic acid, hydrochloric acid, nitric acid, phosphoric acid, hypophosphorous acid, phosphorous acid, phosphonic acid, sulfuric acid, boric acid, hydrofluoric acid, orthophosphoric acid, pyrophosphoric acid, polyphosphoric acid, metaphosphoric acid, hexametaphosphoric acid, etc. Among these, inorganic acids are preferred, nitric acid, sulfuric acid, and hydrochloric acid are more preferred, nitric acid and hydrochloric acid are even more preferred, and hydrochloric acid is particularly preferred.

[0069] In a preferred embodiment of the present invention, the acid that can be used as component (E) includes an inorganic acid. The content of the inorganic acid relative to the total mass of component (E) is preferably 50 mass% or more, and more preferably 90 mass% or more (upper limit 100 mass%). The acid that is component (E) is further preferably an inorganic acid.

[0070] In a further preferred embodiment of the present invention, the component (E) contains at least one acid selected from the group consisting of carbonic acid, hydrochloric acid, nitric acid, phosphoric acid, hypophosphorous acid, phosphorous acid, phosphonic acid, sulfuric acid, boric acid, hydrofluoric acid, orthophosphoric acid, pyrophosphoric acid, polyphosphoric acid, metaphosphoric acid, and hexametaphosphoric acid (hereinafter also referred to as component (E1)). The content ratio of component (E1) to the total mass of component (E) is preferably 50 mass% or more, more preferably 90 mass% or more (upper limit 100 mass%). It is further preferred that the acid of component (E) is component (E1).

[0071] The component (E) may be a commercially available product or a synthetic product. The component (E) may be a single acid or a combination of two or more acids.

[0072] The content of component (E) in the ceramic particle-containing composition is not particularly limited, but it is preferably an amount that causes the pH of the composition at 25° C. to be within the preferred range described below.

[0073] <(F) Ingredient: Thickener> The ceramic particle-containing composition according to the present invention may further contain a thickener as component (F). The viscosity of the ceramic particle-containing composition can be adjusted by the component (F). In this specification, the thickener refers to a compound that has the function of increasing the viscosity of the ceramic particle-containing composition.

[0074] The thickener is preferably a compound capable of achieving a viscosity of 1 Pa·s or more at 25°C in a thickening effect test. Also, it is more preferable that the thickener is a compound capable of achieving a viscosity of 5 Pa·s or more at 25°C in a thickening effect test, and it is even more preferable that the thickener is a compound capable of achieving a viscosity of 10 Pa·s or more at 25°C in a thickening effect test. It is preferable that component (F) contains the compounds listed above. It is preferable that the compounds that become component (B) and the compounds that become component (C) are each compounds that have a viscosity of less than 1 Pa·s at 25°C in a thickening effect test. However, the compounds that become component (B) and the compounds that become component (C) are not limited to such compounds.

[0075] The thickening effect test is performed as follows. First, an aqueous dispersion (a dispersion consisting of alumina particles and water) of alumina particles (product name: WA#30000, manufactured by Fujimi Incorporated Co., Ltd., average secondary particle diameter is 0.3 μm) with an alumina particle concentration of 25 mass% is prepared, and 100 g of this aqueous dispersion with an alumina particle concentration of 25 mass% is added to 5 g of hydrochloric acid solution with a concentration of 2.5 mass% while stirring. Next, a test compound is added to the obtained aqueous dispersion (aqueous dispersion containing alumina particles and hydrochloric acid) in an amount of 4 parts by mass or less per 100 parts by mass of alumina particles. Then, the viscosity of the aqueous dispersion of alumina particles after the test compound is added is measured at 25°C. In the thickening effect test, the judgment is made based on the maximum viscosity value at 25°C when the test compound is added in a range of 4 parts by mass or less per 100 parts by mass of alumina particles. The viscosity of the aqueous dispersion of alumina particles can be measured in the same manner as the viscosity of the ceramic particle-containing composition at 25°C.

[0076] The (F) component is not particularly limited, and a known thickener can be used. The thickener that can be used as the (F) component may be an ionic thickener or a nonionic thickener. The ionic thickener may be an anionic thickener or a cationic thickener. The thickener is preferably an ionic thickener, more preferably a cationic thickener containing a polymer having a (meth)acryloyl group, even more preferably a W / O emulsion containing a poly(meth)acrylic acid ester-based cationic polymer (e.g., a cationic polymer containing a (meth)acrylic acid ester structural unit), and particularly preferably a W / O emulsion containing a polymethacrylic acid ester-based cationic polymer (e.g., a cationic polymer containing a methacrylic acid ester structural unit). The (F) component preferably contains a thickener as listed above. Here, the (meth)acryloyl group is a general term for an acryloyl group and a methacryloyl group. The (meth)acrylic acid ester is a general term for acrylic acid ester and methacrylic acid ester.

[0077] The component (F) may be a commercially available product or a synthetic product. Examples of commercially available products include, but are not limited to, Senka Act Gel AP200, Senka Act Gel NS100, Senka Act Gel CM100, and Senka Act Gel CD100 manufactured by Senka Corporation.

[0078] As the component (F), one type of thickener may be used alone, or two or more types of thickeners may be used in combination.

[0079] When component (F) is used, the content of component (F) in the ceramic particle-containing composition is not particularly limited, but it is preferably an amount such that the viscosity of the ceramic particle-containing composition at 25°C falls within the preferred range described below.

[0080] <Component (G): Components other than components (A) to (F) above> The ceramic particle-containing composition according to one embodiment of the present invention may further contain, as component (G), a component other than the above components (A) to (F), as long as the effect of the present invention is not impaired. The component (G) is not particularly limited, but examples thereof include a base (basic compound, alkali), a salt, a chelating agent, an antifoaming agent, an organic solvent, and the like.

[0081] The content of component (G) is not particularly limited as long as it is within a range in which the effects of the present invention can be obtained, but it is preferably less than 10 mass %, more preferably less than 5 mass %, and even more preferably less than 3 mass %, relative to the total mass of the ceramic particle-containing composition.

[0082] <Total solids concentration of the composition> The total solid content concentration of the ceramic particle-containing composition according to one embodiment of the present invention is not particularly limited, but is preferably 20% by mass or more, more preferably 25% by mass or more, and even more preferably 30% by mass or more. The total solid content concentration of the ceramic particle-containing composition is not particularly limited, but is preferably 60% by mass or less, more preferably 50% by mass or less, and even more preferably 45% by mass or less. If the total solid content concentration is within such a range, the viscosity is appropriate for coating, and a good quality green sheet without cracks or bubbles can be produced. For these reasons, the total solid content concentration of the ceramic particle-containing composition may be 20% by mass or more and 60% by mass or less, 25% by mass or more and 50% by mass or less, 30% by mass or more and 45% by mass or less, but is not limited thereto.

[0083] <ph> The pH of the ceramic particle-containing composition according to one embodiment of the present invention at 25°C is preferably 3.0 or more. The pH of the ceramic particle-containing composition at 25°C is more preferably more than 3.0, and even more preferably 3.1 or more. In these ranges, the occurrence of bleeding out of some components during the formation of a ceramic sintered body can be further suppressed. The pH of the ceramic particle-containing composition at 25°C is preferably 12.0 or less, more preferably 9.0 or less, even more preferably 7.0 or less, and particularly preferably 5.5 or less. In these ranges, thickening due to dehydration condensation of the resin used as a binder can be further suppressed, and the possibility of excessive thickening of the composition is further reduced, making the composition more suitable for coating.

[0084] The pH of the ceramic particle-containing composition at 25° C. can be measured using a pH meter, specifically, by the method described in the Examples. From these, the pH of the ceramic particle-containing composition at 25° C. can be, but is not limited to, 3.0 to 12.0, 3.0 to 9.0, more than 3.0 to 7.0, or 3.1 to 5.5.

[0085] <Viscosity> The viscosity of the ceramic particle-containing composition at 25°C is not particularly limited, but is preferably 0.01 Pa·s or more, more preferably 0.03 Pa·s or more, and even more preferably 0.05 Pa·s or more. The viscosity of the ceramic particle-containing composition at 25°C is not particularly limited, but is preferably 5 Pa·s or less, more preferably 3 Pa·s or less, and even more preferably 2 Pa·s or less. When the viscosity is in such a range, a prepreg having excellent dispersibility of unidirectional ceramic fibers with the above-mentioned coefficient of variation of 2.0 or less can be obtained. In addition, the coating property of the ceramic particle-containing composition is further improved, and the impregnation of the composition into the ceramic fibers becomes easier. The viscosity of the ceramic particle-containing composition at 25°C can be measured using a B-type viscometer, and specifically, it can be measured by the method described in the examples. For these reasons, examples of the viscosity range of the ceramic particle-containing composition at 25° C. include, but are not limited to, 0.01 Pa·s or more and 5 Pa·s or less, 0.03 Pa·s or more and 3 Pa·s or less, and 0.05 Pa·s or more and 2 Pa·s or less. The viscosity can be controlled by the type and content of each component in the ceramic particle-containing composition, the total solids concentration, etc.

[0086] <Method of producing the composition> The method for producing the ceramic particle-containing composition is not particularly limited, and may include, for example, mixing component (A): ceramic particles, component (B): binder, component (C): plasticizer, and component (D): water. The method for producing the ceramic particle-containing composition may further include mixing other components (e.g., the above-mentioned components (E), (F), and (G)) as necessary.

[0087] The component (A) is preferably added as a dispersion containing the components (A) and (D). The component (B) is preferably added as a dispersion containing the components (B) and (D). Therefore, the method for producing the composition preferably includes mixing a dispersion containing the components (A) and (D), a dispersion containing the components (B) and (D), and at least one selected from the group consisting of the component (C), a solution containing the component, and a dispersion containing the component.

[0088] [Prepreg manufacturing method] The manufacturing method of the unidirectional ceramic fiber prepreg according to one embodiment of the present invention is not particularly limited, but is preferably a manufacturing method including the steps of (1) preparing a plurality of ceramic fibers oriented in one direction and a ceramic particle-containing composition, (2) applying the ceramic particle-containing composition onto a support to obtain a coating film, (3) immersing the plurality of ceramic fibers oriented in one direction into the coating film to obtain a ceramic particle-containing composition-impregnated body, and (4) drying the ceramic particle-containing composition-impregnated body, and then peeling off the support to obtain a unidirectional ceramic fiber prepreg. Each step will be described below.

[0089] <(1) Step of preparing a composition containing a plurality of ceramic fibers oriented in one direction and ceramic particles> In this step, unidirectional ceramic fibers are prepared. The method is not particularly limited, but a method of opening a bundle of ceramic fibers is preferred. Opening is an operation of splitting a bundle of converged ceramic fibers, which is expected to have the effect of further increasing the impregnation of the ceramic particle-containing composition.

[0090] When the ceramic fiber bundle is spread, it is preferable to use a fiber spreading device. The fiber spreading method is not particularly limited, and known methods such as a method of alternately passing the bundle through uneven rolls, a method of using a drum-shaped roll, a method of adding tension fluctuation to axial vibration, a method of varying the tension of the fiber bundle by multiple friction bodies that reciprocate vertically, a method of blowing air onto the fiber bundle, a method of sucking the fiber bundle with air, a method of using a spring fiber spreading element, a method of using an expander roll, and the like can be used alone or in appropriate combination.

[0091] In this step, a ceramic particle-containing composition is prepared. The method for preparing the ceramic particle-containing composition is as described above, and therefore will not be described here.

[0092] <(2) Step of applying the ceramic particle-containing composition onto a support to obtain a coating film> In this step, the ceramic particle-containing composition prepared in the above step (1) is applied onto a support to obtain a coating film.

[0093] As the support, a film made of a resin material is preferably used. Examples of the resin material include polyester resins such as polyethylene terephthalate (PET) and polyethylene naphthalate (PEN), polycarbonate (PC) resin, acrylic resins such as polymethyl methacrylate (PMMA), cyclic olefin polymer (COP), triacetyl cellulose (TAC) resin, polyethersulfone (PES) resin, polyetherketone (PEK) resin, polyimide (PI) resin, etc. Among these, polyethylene terephthalate (PET) is preferable. The film made of the resin material may be subjected to a surface treatment such as corona treatment, atmospheric pressure plasma treatment, vacuum plasma treatment, and primer coating treatment.

[0094] The method for applying the ceramic particle-containing composition may be, for example, a known method such as a bar coater method, an applicator method, a curtain flow coater method, a roll coater method, a spray method, a gravure coater method, a comma coater method, a reverse roll coater method, a lip coater method, a die coater method, a slot die coater method, an air knife coater method, a dip coater method, etc. Among these, the applicator method is preferred.

[0095] The thickness of the coating film is preferably from 10 μm to 2000 μm, more preferably from 50 μm to 1800 μm, and even more preferably from 100 μm to 1500 μm. By adjusting the thickness of the coating film, the fiber content (Vf) of the unidirectional ceramic fibers in the prepreg can be controlled to a desired value.

[0096] After the coating film is formed, the coating film may be dried if necessary, but it is preferable to immerse the unidirectional ceramic fibers in the coating film without drying.

[0097] <(3) A step of immersing a plurality of ceramic fibers oriented in one direction into the coating film to obtain a ceramic particle-containing composition-impregnated body> In this step, unidirectional ceramic fibers are immersed in the coating film obtained in the above step (2) to obtain a ceramic particle-containing composition-impregnated body.

[0098] When the unidirectional ceramic fibers are immersed, they may or may not be fixed in place using a resin or metal frame.

[0099] The temperature of the coating film during immersion (immersion temperature) is not particularly limited and is usually in the range of 10° C. to 40° C. The immersion time is also not particularly limited and is usually 0.5 minutes to 10 minutes. After immersion, the ceramic particle-containing composition is impregnated into the unidirectional ceramic fibers, and a ceramic particle-containing composition-impregnated body with the support still attached is obtained.

[0100] <(4) Step of drying the ceramic particle-containing composition impregnated body to obtain a prepreg> In this step, the ceramic particle-containing composition-impregnated body obtained in the above step (3) is dried, and then the support is peeled off to obtain a unidirectional ceramic fiber prepreg.

[0101] The drying method is not particularly limited, and examples thereof include heat drying, hot air drying, etc. In the case of heat drying, the drying temperature is preferably in the range of 70° C. to 140° C., and the drying time is preferably in the range of 10 minutes to 60 minutes.

[0102] After drying, the support is peeled off to obtain a unidirectional ceramic fiber prepreg. The thickness of the obtained unidirectional ceramic fiber prepreg is not particularly limited, but is preferably 10 μm to 500 μm, more preferably 20 μm to 300 μm, and even more preferably 50 μm to 200 μm. The width and length of the unidirectional ceramic fiber prepreg can be appropriately set depending on the application.

[0103] By using a manufacturing method including a sintering process for sintering the unidirectional ceramic fiber prepreg thus obtained, it is possible to obtain a ceramic matrix composite material (CMC) in which ceramic fibers are used as a reinforcing material and the matrix is ​​also made of a ceramic material. Such a ceramic matrix composite material is considered to have excellent mechanical properties.

[0104] Although the embodiments of the present invention have been described in detail, it is apparent that the same are illustrative and exemplary, and not restrictive, and the scope of the present invention should be interpreted by the appended claims.

[0105] The present invention encompasses the following aspects and configurations: 1. A method for producing a unidirectional ceramic fiber prepreg, comprising the steps of: preparing a plurality of unidirectionally oriented ceramic fibers and a ceramic particle-containing composition; applying the ceramic particle-containing composition onto a support to obtain a coating film; immersing the plurality of unidirectionally oriented ceramic fibers into the coating film to obtain a ceramic particle-containing composition-impregnated body; and drying the ceramic particle-containing composition-impregnated body and then peeling off the support to obtain a unidirectional ceramic fiber prepreg: 2. A method for producing a unidirectional ceramic fiber prepreg according to the above item 1, wherein the viscosity of the ceramic particle-containing composition at 25°C is 0.01 Pa s or more and 5 Pa s or less: 3. The method for producing a unidirectional ceramic fiber prepreg according to 1. or 2. above, wherein the thickness of the coating film is 10 μm or more and 2000 μm or less: 4. A unidirectional ceramic fiber prepreg comprising a plurality of ceramic fibers oriented in one direction and a ceramic particle-containing composition impregnated into the plurality of ceramic fibers, wherein a coefficient of variation in the number of the ceramic fibers per unit section in a cut surface along the thickness direction of the unidirectional ceramic fiber prepreg is 2.0 or less: 5. The unidirectional ceramic fiber prepreg according to 4 above, wherein the coefficient of variation is 1.7 or less. 6. The unidirectional ceramic fiber prepreg according to 4. or 5. above, wherein the ceramic fibers are silicon carbide fibers, alumina fibers, mullite fibers, or carbon fibers. 7. The unidirectional ceramic fiber prepreg according to any one of 4. to 6. above, wherein the ceramic particles contained in the ceramic particle-containing composition are at least one selected from the group consisting of alumina particles, silicon carbide particles, and silicon carbide particles coated with a coating layer containing aluminum hydroxide. 8. The unidirectional ceramic fiber prepreg according to any one of 4. to 7. above, wherein the fiber content of the ceramic fibers in the unidirectional ceramic fiber prepreg is 20 volume % or more and 85 volume % or less. EXAMPLES

[0106] The present invention will be described in more detail using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. Unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively. In the following examples, unless otherwise specified, the operations were performed under the conditions of room temperature (25°C) / relative humidity of 40% RH or more and 50% RH or less.

[0107] The physical properties were measured by the following methods.

[0108] (Average secondary particle size of ceramic particles) The average secondary particle size of the ceramic particles was determined by a dynamic light scattering method using a particle size distribution measuring device (UPA-UT151, manufactured by Nikkiso Co., Ltd.) and was measured as the volume average particle size.

[0109] (pH Measurement) The pH of the ceramic particle-containing composition was measured at 25° C. using a pH meter (model number: F-71) manufactured by Horiba, Ltd.

[0110] (Viscosity measurement) The viscosity of the ceramic particle-containing composition was measured at 25° C. using a B-type viscometer manufactured by Toki Sangyo Co., Ltd. (model number: TVB-10, rotor No. 27, rotor rotation speed: 60 rpm).

[0111] (Weight average molecular weight measurement of binder) The weight average molecular weight (Mw) of the binder contained in the ceramic particle-containing composition was measured by gel permeation chromatography (GPC) under the following measurement conditions, expressed as a polyethylene oxide equivalent value: <GPC measurement conditions> Sample concentration: 0.1% by mass Column: "TSKgel GMPWXL" manufactured by Tosoh Corporation Detector: Differential refractometer Eluent: 100mM sodium nitrate aqueous solution Flow rate: 1mL / min Measurement temperature: 40℃ Sample injection volume: 200 μL Measuring device: "HLC-8320GPC" manufactured by Tosoh Corporation.

[0112] (Measurement of molecular weight of plasticizer) The average molecular weight of the plasticizer was calculated from the results of measuring the hydroxyl value by neutralization titration method based on JIS K 0070: 1992. More specifically, the calculation was performed according to the following procedure: (1) Procedure: For 0.6 g of plasticizer, the hydroxyl value was determined according to JIS K 0070:1992 "Testing method for acid value, saponification value, ester value, iodine value, hydroxyl value and unsaponifiable matter of chemicals 7.1 Neutralization titration method"; (2) Calculation: The average molecular weight was calculated from the following formula: A = (56106 / B) x 2 A: Average molecular weight B: Hydroxyl value obtained in (1) above (unit: mgKOH / g) 56106: Coefficient based on the molecular weight of potassium hydroxide.

[0113] [Prepreg manufacturing] <Preparation of unidirectionally oriented carbon fibers> The carbon fiber bundle was opened using a fiber opening device to prepare a plurality of carbon fibers oriented in one direction.

[0114] <Aluminum hydroxide coated silicon carbide (SiC) particles> A 20% by mass aqueous dispersion of silicon carbide (SiC) particles (GC#40000, average secondary particle diameter 0.36 μm, Fujimi Incorporated, powder) was prepared, and 1M NaOH aqueous solution was added to the dispersion to obtain a pH of 10.0. Next, a 30% by mass aqueous dispersion of sodium aluminate was prepared, and an aqueous dispersion of sodium aluminate in an amount of 50 parts by mass of sodium aluminate per 100 parts by mass of silicon carbide particles and 9.9% by mass nitric acid were added over 45 minutes while stirring to maintain a pH of 9.0 to 11.0. After stirring for another 45 minutes, 9.9% by mass nitric acid was added to obtain a pH of 10.5 of the dispersion, and an aqueous dispersion containing silicon carbide (SiC) particles coated with aluminum hydroxide was prepared. Then, 9.9% by mass nitric acid was added to obtain a pH of 3.0, and the mixture was concentrated by suction filtration to obtain an aqueous dispersion of aluminum hydroxide-coated SiC particles with a concentration of 40% by mass.

[0115] <Analysis of composition and structure of particles in aqueous dispersion> The fact that the particles in the dispersion obtained above were aluminum hydroxide-coated SiC particles was confirmed by the following analysis.

[0116] Approximately 2 mL of the aqueous dispersion obtained above was collected and dropped onto a filter (Nuclepore 5 μm) (manufactured by WHATMAN). Then, suction filtration was performed, and the powder was washed on the filter using 10 mL of pure water, and the particles were dried. The dried particles were then collected on a Si wafer and observed by SEM (Scanning Electron Microscope)-EDX (Energy Dispersive X-ray Spectroscopy) using a scanning electron microscope SU-8000 manufactured by Hitachi High-Technologies Corporation.

[0117] In addition, the dried particles were collected on a carbon tape and subjected to EELS (Electron Energy Loss Spectroscopy) analysis using TITAN80-300 manufactured by FEI.

[0118] In SEM-EDX observation of the particles, C, Al, and O were selected as the elements to be observed, and the EDX spectrum of Al was observed. It was also confirmed that the positions where the EDX spectra of C, Al, and O were observed clearly corresponded to the positions where the particles were observed in the SEM observation image. Therefore, it was determined that the SiC particles were coated with a component containing Al and O.

[0119] In addition, in the EELS analysis of the particles, it was confirmed that the observed EELS spectrum had a spectral shape specific to the standard EELS spectrum of aluminum hydroxide (Al(OH)3) (a shape different from the spectra of Al and other compounds containing Al and O). Therefore, it was determined that the components containing Al and O included Al(OH)3.

[0120] <Preparation of ceramic particle-containing composition> The aluminum hydroxide-coated silicon carbide particles obtained above, a 20% by mass aqueous dispersion of polyvinyl acetal (water-soluble polymer, product name: S-LEC (registered trademark) KW-3, manufactured by Sekisui Chemical Co., Ltd., polymerization degree of about 600, weight average molecular weight of 1,000 or more) as a binder resin, a polyethylene glycol (PEG200, number average molecular weight: 200, weight average molecular weight less than 1000, manufactured by Fujifilm Wako Pure Chemical Industries Co., Ltd.) as a plasticizer, and an Olfine (registered trademark) E1004 (manufactured by Nissin Chemical Industry Co., Ltd.) as a defoamer were added to a container in a quantity ratio such that the solid content ratio is as shown in Table 1 below. Then, a rotation-revolution type mixer (Awatori Rentaro, ARE-310, manufactured by Thinky Corporation) was used to stir at 1400 rpm for 2 minutes to obtain a ceramic particle-containing composition with a total solid content concentration of 35.5% by mass.

[0121] The resulting ceramic particle-containing composition had a pH of 3.86 and a viscosity of 85 mPa·s at 25°C.

[0122] [Table 1]

[0123] (Example) A polyethylene terephthalate (PET) film (Lumirror (registered trademark) S10, film thickness 100 μm, manufactured by Toray Industries, Inc.) was prepared as a support. This PET film was set in a coating machine (IMC-7373, manufactured by Imoto Manufacturing Co., Ltd.), and the ceramic particle-containing composition obtained above was applied onto the PET film using an applicator to obtain a coating film having a thickness of 450 μm.

[0124] The above-prepared multiple unidirectionally oriented carbon fibers were immersed in the resulting coating film at a temperature of 25° C. for 1 minute to obtain a ceramic particle-containing composition-impregnated body.

[0125] The obtained ceramic particle-containing composition-impregnated body was placed in a Lightspec thermohygrostat (model number: LU-114, manufactured by Espec Corporation) set at 90°C and dried for 20 minutes. After drying, the PET film support was peeled off to obtain a unidirectional ceramic fiber prepreg with a thickness of 137 μm. The fiber content (Vf) of carbon fiber in the obtained unidirectional ceramic fiber prepreg was 45.8 volume %.

[0126] [Calculation of coefficient of variation] The unidirectional ceramic fiber prepreg obtained above was cut in the thickness direction using a vertical slicer (model number: HS-1-S, manufactured by JUSCO Engineering Co., Ltd.) to a size of about 10 mm x about 10 mm. The cut surface of the cut prepreg was photographed using a low vacuum scanning electron microscope (model number: JSM-IT100, manufactured by JEOL Ltd., magnification 500 times). The photographed area was 192 μm long x 256 μm wide.

[0127] The photograph was imported into the software Jw-cad, and the photographed area was divided vertically into 4 parts relative to the entire thickness of the prepreg, and horizontally into 4 parts with a width of 256 μm. This resulted in a total of 16 sections, and the number of carbon fibers per section was counted for each section. The standard deviation and average value were calculated for the number of carbon fibers in the 16 measured sections. The coefficient of variation of the unidirectional ceramic fibers was calculated by dividing the standard deviation value by the average value, which was 1.247.

[0128] Fig. 1 is a SEM photograph of a cut surface along the thickness direction of the unidirectional ceramic fiber prepreg obtained in this example. As is clear from Fig. 1, it was found that the dispersion of the unidirectional carbon fibers is good in the prepreg obtained in this example. This suggests that the ceramic-based composite material produced by using the prepreg obtained in this example may have excellent mechanical properties.

[0129] (Comparative Example) A ceramic particle-containing composition was prepared in the same manner as in the above-mentioned Example, and an immersion bath for the obtained ceramic particle-containing composition was prepared. A plurality of carbon fibers oriented in one direction, prepared in the same manner as above, were immersed in the prepared immersion bath at a temperature of 25°C for 2 minutes. The carbon fibers removed after immersion showed signs of fiber bundling and gap formation, and had very low dispersibility, making them unusable as prepregs.< / ph>

Claims

1. Providing a composition containing a plurality of unidirectionally oriented ceramic fibers and ceramic particles; A step of applying the ceramic particle-containing composition onto a support to obtain a coating film; A step of immersing the plurality of ceramic fibers oriented in one direction into the coating film to obtain a ceramic particle-containing composition-impregnated body; and a step of drying the ceramic particle-containing composition-impregnated body and then peeling off the support to obtain a unidirectional ceramic fiber prepreg; A method for producing a unidirectional ceramic fiber prepreg, comprising:

2. The method for producing a unidirectional ceramic fiber prepreg according to claim 1, wherein the viscosity of the ceramic particle-containing composition at 25°C is 0.01 Pa·s or more and 5 Pa·s or less.

3. 3. The method for producing a unidirectional ceramic fiber prepreg according to claim 1, wherein the coating film has a thickness of 10 μm or more and 2000 μm or less.

4. A plurality of ceramic fibers oriented in one direction; a ceramic particle-containing composition impregnated into the plurality of ceramic fibers; A unidirectional ceramic fiber prepreg comprising: A unidirectional ceramic fiber prepreg, wherein a coefficient of variation in the number of the ceramic fibers per unit section in a cut section along a thickness direction of the unidirectional ceramic fiber prepreg is 2.0 or less.

5. The unidirectional ceramic fiber prepreg according to claim 4 , wherein the coefficient of variation is 1.7 or less.

6. The unidirectional ceramic fiber prepreg according to claim 4 or 5, wherein the ceramic fibers are silicon carbide fibers, alumina fibers, mullite fibers, or carbon fibers.

7. 6. The unidirectional ceramic fiber prepreg according to claim 4 or 5, wherein the ceramic particles contained in the ceramic particle-containing composition are at least one type selected from the group consisting of alumina particles, silicon carbide particles, and silicon carbide particles coated with a coating layer containing aluminum hydroxide.

8. 6. The unidirectional ceramic fiber prepreg according to claim 4, wherein the fiber content of the ceramic fibers in the unidirectional ceramic fiber prepreg is 20% by volume or more and 85% by volume or less.

Citation Information

Patent Citations

  • Method for manufacturing ceramic matrix composite member, and die device for manufacturing ceramic matrix composite member

    JP6978896B2